Prototype of Gas Warning Monitoring Application Using Mobile Android Smartphone : A Case Study - Diki Hermawan; Eko Budi Setiawan (IJNMT (International Journal of New Media Technology), 2017)
This study aims to monitor gas leakage with case studies in a national company engaged in the production of polycarbonate for drinking water packaging. In the future this research will be referred to as the Company. The Company implements Sistem Manajemen Keselamatan dan Kesehatan Kerja or socalled. System Management K3 (SMK3) to create a safety and health system by involving elements of management, labor, conditions and an integrated work environment in order to prevent and reduce accidents and occupational diseases. One of the causes of work accidents of the many causes that should be a concern is the danger that can be caused by the leaking gas LPG installation. Such hazards may cause explosions to fire that may threaten the safety of workers in companies using LPG gas for their production processes. The system in this study was designed to monitor and provide gas leak warnings to leaked LPG gas installations and promptly take prompt and automatic precautions. With the development of warning gas monitoring via android raspberry-based pi is expected to improve the security system and reduce therisk of work accident caused by LPG gas. Index Terms— Gas Monitoring, Raspberry pi, MQ2, LPG, Android REFERENCES[1] F. Pangkey dan G. Y. Malingkas, “Jurnal Ilmiah MEDIA ENGGINEERING,” Penerapan Sistem ManajemenKeselamatan Dan Kesehatan Kerja (SMK3) Pada Proyek Konstruksi Di Indonesia , vol. 2 , pp. 100-113, 2012.[2] B. Hadiwijaya, D. dan A. A. Zahra, “TRANSIENT,” Perancangan Aplikasi CCTV Sebagai Pemantau RuanganMenggunakan IP Camera, vol. 3, p. 232, 2014.[3] R. F. Giant, “Perancangan Aplikasi Pemantau Dan Pengendali Piranti Elektronik Pada Ruangan BerbasisWeb,” TRANSMISI , vol. 2, pp. 71-74, 2015.[4] S. Paul, A. Antony. , “International Journal Of Computing and Technology,” Android Based Home AutomationUsing Raspberry Pi , vol. 1, pp. 143-147, 2014.[5] M. P. Sulistyanto, D. A. Nugraha, N. Sari, N. Karima dan W. Asrori, “Implementasi IOT (Internet Of Things) dalam Pembelajaran di Universitas Kanjuruan Malang,” SMARTICS Journal , vol. 1, pp. 20-23, 2015.[6] H. N. Lengkong, “Perancangan Penunjuk Rute Pada Kendaraan Pribadi Menggunkan Aplikasi GIS BerbasisAndroid Yang Terintregasi Pada Google Maps,” EJournal Teknik Elektro dan Komputer, vol. 1, pp. 20-21,2015.[7] B. Prakasa, M. S. Qiron dan D. Hermanto, “Automatisasi Smart Home Dengan Rasperry Pi Dan SmartphoneAndroid,” pp. 1-13.[8] D. Nurmali dan S. Suhartini, “Komunikasi Data Digital menggunakan Gelombang Radio HF,” Penelitian PusatPemamfaatan Sains Antartika Lapan , vol. 1, pp. 27-30,2005.